Comparative evaluation of mucin and total protein in periodontal disease before and after nonsurgical periodontal therapy - J. P. Vishnu; Anju Gautam; Surendra Pratap Mishra; Farhan Durrani; Fouzia Imran; Ekta Kumari (Wolters Kluwer Medknow Publications, 2024)
Background: Periodontal ailments cause a quantum leap in the biomarker profile of the saliva. This profile is, in fact, the epiphany of the scale and extent of the disease. Both gingivitis and periodontitis are chronic inflammatory diseases with a step-grade progression. The study aimed to determine the response of the host in these conditions by analyzing concentrations of salivary mucin and total protein activity, before and after nonsurgical periodontal therapy (NSPT). Materials and Methods: Sixty adult subjects were clinically examined and divided into three groups (n = 20) according to the clinical assessment and categorized as Group I (healthy), Group II (gingivitis), and Group III (chronic periodontitis). Whole saliva was collected, and salivary mucin and total protein levels were quantitatively measured at baseline in all the groups and additionally after NSPT in Groups II and III. Results: Levels of mucin and total protein increased in patients with gingivitis and periodontitis. There was a slight decline in mucin levels in periodontitis patients in comparison with the gingivitis group. A positive correlation was found between the respective clinical parameters of both the groups along with their levels of salivary mucin and total protein. It indicated that the response of salivary glands to increase their protective potential caused the change among the groups. Conclusion: Periodontal diseases induce an increase in the levels of mucins and proteins, which is believed as the action of the salivary glands to protect the oral cavity and put off the chaos caused by the microorganisms.